2003
DOI: 10.1002/joc.916
|View full text |Cite
|
Sign up to set email alerts
|

A 10 year cloud climatology over Scandinavia derived from NOAA Advanced Very High Resolution Radiometer imagery

Abstract: Results from a satellite-based method to compile regional cloud climatologies covering the Scandinavian region are presented. Systematic processing of multispectral image data from the NOAA Advanced Very High Resolution Radiometer (AVHRR) instrument has been utilized to provide monthly cloud climatologies covering the period 1991-2000. Considerable local-scale variation of cloud amounts was found in the region. The inland Baltic Sea and adjacent land areas exhibited a large-amplitude annual cycle in cloudiness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 21 publications
5
60
0
Order By: Relevance
“…But why does POLDER retrieval tend to be smaller? The underlying physics is as follows: It has been shown that the observed cloud reflectivity at a non-absorbing wavelength, such as the 0.86µm, is generally proportional to the scaled optical thickness, (1 − g)τ , (van de Hulst, 1980;King, 1987). In other words, the retrieved τ is proportional to 1/(1 − g).…”
Section: Comparison Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But why does POLDER retrieval tend to be smaller? The underlying physics is as follows: It has been shown that the observed cloud reflectivity at a non-absorbing wavelength, such as the 0.86µm, is generally proportional to the scaled optical thickness, (1 − g)τ , (van de Hulst, 1980;King, 1987). In other words, the retrieved τ is proportional to 1/(1 − g).…”
Section: Comparison Results and Discussionmentioning
confidence: 99%
“…It plays a key role in determining cloud radiative forcing (CRF) (e.g., Fu and Liou, 1993;Jensen et al, 1994;Fu, 1996;Fu et al, 1998;McFarquhar et al, 2000). A popular method to retrieve cloud τ relies on satellite measurements of the Earth's reflected shortwave radiance (King, 1987;Nakajima and King, 1990;Minnis et al, 1993) (Hereafter it is referred to as the "solar reflective method"). It has been employed in the retrieval algorithms of several satellite instruments, such as the Advanced Very High Resolution Radiometer (AVHRR) (Heidinger et al, 2005), Spinning Enhanced Visible and Infrared Imager (SEVIRI) (Roebeling et al, 2006), MODIS (Platnick et al, 2003) and POLDER (Buriez et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its improved spatial and spectral resolution, it was capable to sense the dynamical changes in coastal water quality, and it also has been shown to improve the temporal resolution of water monitoring programs Harvey et al, 2015), even in areas with relatively frequent cloud cover, such as the Baltic Sea (Isemer and Rozwadowska, 1999;Karlsson, 2003). 30 One parameter that can be used to identify the extent of the coastal zone is total suspended matter (TSM), which also can be detected from space using ocean colour remote sensing data.…”
Section: Introductionmentioning
confidence: 99%
“…These long-term measurements at high spatio-temporal resolution and at carefully chosen spectral wavelengths make them extremely valuable for climate monitoring purposes and process-based studies (Rossow and Schiffer, 1999;Karlsson, 2003;Heidinger and Pavolonis, 2009;Schulz et al, 2009). The AVHRR data in principle could be used for investigating variability and trends in essential climate variables at the decadal time scales.…”
Section: Introductionmentioning
confidence: 99%